Roux-en-Y versus single loop reconstruction in pancreaticoduodenectomy: A systematic review and meta-analysis. (April 2021) - Mobarak, Shahd; Tarazi, Munir; Davé, Madhav Sanatkumar; Varley, Rebecca J; Stott, Martyn C; Baltatzis, Minas; Satyadas, Thomas
Abstract: Background: Post-operative pancreatic fistula (POPF) and delayed gastric emptying (DGE) both remain problematic complications following pancreaticoduodenectomy. This systematic review and meta-analysis evaluates whether Roux-en-Y compared to a single loop reconstruction in pancreaticoduodenectomy significantly reduces rates of these complications. Methods: A systematic review and meta-analysis was conducted according to the PRISMA guidelines by screening EMBASE, MEDLINE/PubMed, CENTRAL and bibliographic reference lists for comparative studies meeting the predetermined inclusion criteria. Post-operative outcome measures included: POPF, DGE, bile leak, operating time, blood loss, need for transfusion, wound infection, intra-abdominal collection, post-pancreatectomy haemorrhage, overall morbidity, re-operation, overall mortality, hospital length of stay. Pooled odds ratios or mean differences with 95% confidence intervals were calculated using either fixed- or random-effects models. Results: Fourteen studies were identified including four randomised controlled trials (RCTs) and 10 observational studies reporting a total of 2, 031 patients. Data synthesis showed no statistically significant difference between the two groups in any of the outcome measures except operating time, which was longer in those undergoing Roux-en-Y reconstruction. Discussion: Roux-en-Y is not superior to single loop reconstruction in pancreaticoduodenectomy but may prolong operating time. Future high-quality randomised studies with appropriate study design and sample size power calculation may be required to further validate this conclusion. Highlights: There is no difference in complications in Roux-en-Y versus single loop reconstruction in pancreaticoduodenectomy. Performing a Roux-en-Y loop reconstruction increases operating time compared to a single loop. Rates of post-operative pancreatic fistula and delayed gastric emptying are not improved with a Roux-en-Y anastomosis.